Binder Jetting Additive Manufacturing: Powder Packing in Shell Printing - Guanxiong Miao; Mohammadamin Moghadasi; Ming Li; Zhijian Pei; Chao Ma (Journal of Manufacturing and Materials Processing, 2022)
Shell printing is an advantageous binder jetting technique that prints only a thin shell of the intended object to enclose the loose powder in the core. In this study, powder packing in the shell and core was investigated for the first time. By examining the density and microstructure of the printed samples, powder packing was found to be different between the shell and core. In addition, the powder particle size and layer thickness were found to affect the powder packing in the shell and core differently. At a 200 µm layer thickness, for the 10 µm and 20 µm powders, the core was less dense than the shell and had a layered microstructure. At a 200 µm layer thickness, for the 70 µm powder, the core was denser and had a homogeneous microstructure. For the 20 µm powder, by reducing the layer thickness from 200 µm to 70 µm, the core became denser than the shell, and the microstructure of the core became homogeneous. The different results could be attributed to the different scenarios of particle rearrangement between the shell and core for powders of different particle sizes and at different layer thicknesses. Considering that the core was denser and more homogeneous than the shell when the proper layer thickness and powder particle size were selected, shell printing could be a promising method to tailor density and reduce anisotropy.